A temperature shift during embryogenesis impacts prevalence of deformity in diploid and triploid Atlantic salmon (Salmo salar L.). (23rd October 2020) - Clarkson, Michael; Taylor, John Frank; McStay, Elsbeth; Palmer, Matthew John; Clokie, Benjamin Gregory James; Migaud, Hervé
Abstract: The study investigated the effects of a temperature shift during embryogenesis on diploid and triploid Atlantic salmon ( Salmo salar L.) embryo development and juvenile skeletal deformities. From fertilization, sibling populations were incubated under one of three temperatures (6, 8 or 11°C) until 400 °days when all fish were then reared under a common temperature until smolt. Survival was negatively impacted by increasing temperatures irrespective of ploidy. There was no effect of incubation temperatures on growth in diploids, but triploids incubated at 6°C had improved growth rates (thermal growth coefficient, TGC: 6°C: 1.05, 8°C: 0.94, 11°C: 0.48). Fish from 11°C in both ploidies showed increased jaw and vertebral deformity prevalence. In response to the temperature change at 400 °days post fertilization, upregulation of bmp2, bmp4, col2a1, mmp13, opn and sparc, and downregulation of ocn further suggest that bone and cartilage formation is compromised after experiencing a thermal shift. The data show that temperature profile during embryogenesis strongly influences future growth and deformity prevalence. Triploids appear to require a lower incubation temperature than the current industry standard of 8°C to promote better overall performance; however, a thermal shift during embryogenesis was shown to impact expression of important developmental genes.